COMORBIDITY OF DIABETIC RETINOPATHY AND METABOLICALLY ASSOCIATED STEATOTIC LIVER DISEASE - Skrypnyk, Rimma; Kozak, Bogdan (Eastern Ukrainian Medical Journal, 2026)
A personalized approach to the early diagnosis and prevention of diabetic retinopathy (DR) in patients with diabetes mellitus (DM) is currently a significant issue that requires investigation of comorbid effects, in particular in metabolic-associated steatotic liver disease (MASLD). This is due to the increase in the incidence of diabetes and complications, such as diabetic retinopathy, which significantly reduces the quality of life and often leads to blindness. Objective: to study the characteristics of the development and course of DR in patients with type 2 diabetes and MASLD.Materials and methods: The study included 62 patients with type 2 diabetes mellitus with DR. Patients were divided into two groups: I - patients with DR and MASLD and II - DR without liver pathology. In addition to general clinical and biochemical tests, all patients were determined by the NOMA index, BMI and liver fibrosis index. Anamnestic data on the occurrence and progression of DM, DR and MASLD were analyzed in detail. Elastography and optical coherence tomography were performed.Results. Nonproliferative diabetic retinopathy was more common than proliferative in both groups, but the degree of damage and the rate of its progression were higher (p<0.001) in patients in the first group. Proliferative diabetic retinopathy was detected with a higher frequency in patients with MASLD. Patients with proliferative DR in both groups had a worse level of diabetes compensation and a higher liver fibrosis index compared to patients with nonproliferative DR. A direct correlation was found between the rate of progression of DR and the level of liver fibrosis in patients with MASLD.Conclusions. The results of the study confirm the comorbidity of MASLD and DR in patients with type 2 diabetes. A direct correlation was found between the degree of liver fibrosis and the rate of progression of DR. Therefore, MASLD screening with determination of the level of fibrosis in patients with type 2 diabetes can be used as one of the markers of the development and progression of DR.